2013
DOI: 10.3343/alm.2013.33.3.208
|View full text |Cite
|
Sign up to set email alerts
|

A Case of IgM Deficiency with B Cell Deficiency Detected by ABO Discrepancy in a Patient with Acute Osteomyelitis

Abstract: ABO discrepancy refers to an inconsistency between red cell and serum typings and has various causes, including hypogammaglobulinemia. IgM deficiency is a rare disorder that may accompany several conditions such as infection and autoimmune disorders. Here, we describe a case of IgM deficiency discovered during the evaluation of an ABO discrepancy in a 16-yr-old Korean boy. ABO blood grouping showed that while his cell type was O+, serum typing detected only anti-A (3+). Anti-B was not detectable at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The use of not washed pRBCs may have allowed the presence of soluble antigens that could have inhibited the antigen‐antibody agglutination reaction . Severe hypogammaglobulinemia (ie, sever IgM deficit) has been reported in human medicine to cause blood typing discrepancy . The apparently healthy condition of this type B cat did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 82%
“…The use of not washed pRBCs may have allowed the presence of soluble antigens that could have inhibited the antigen‐antibody agglutination reaction . Severe hypogammaglobulinemia (ie, sever IgM deficit) has been reported in human medicine to cause blood typing discrepancy . The apparently healthy condition of this type B cat did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, Subramanian et al concluded that rarely patients with carcinoma and lymphoma can develop excess serum blood group substances, able to deactivate the typing antisera. 28,29 Since the pretransplant antibody removal and standard immunosuppressive drug medicine as the only additional pretreatment was postulated to be insufficient when using group A1 and B donors, 30 the use of donor plasma able to inhibit agglutination and haemolysis of erythrocytes (as was revealed in the present study) might be important in ABO incompatible transplantation. Whether the use of the plasma of the donors with type II-III of ABO discrepancy will increase the long-term graft survival in ABO incompatible transplantation remains to be shown.…”
Section: Discussionmentioning
confidence: 68%
“…14,28,29 Type III discrepancies were found in persons with modification of blood group type: a person of O blood group with anti-A (1:8 titre) and anti-B antibodies (1:4 titre) after allogeneic group AB transplantation for juvenile myelomonocytic leukaemia showed modification of blood group type: the forward typing demonstrated conversion to AB blood group (anti-A and anti-B reagents showed weak mixed-field agglutination). 17,30 Type III discrepancy was observed in persons with Hodgkin lymphoma, cord blood and plasma exchange with dextran or polyvinyl pyrrolidone.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, we evaluate B and T-lymphocyte subsets in patients with AIS at diagnosis and 3 months after antibacterial treatment. To our knowledge, there are no prior studies of the immune system in patients with AIS or osteomyelitis, although there are casuistic reports of rare cases leading to evaluation of immunologic status 11 13 and in chronic osteomyelitis, studies have dealt with the interaction between immunological cells, bone resorption and treatment effect 14 – 18 .…”
Section: Discussionmentioning
confidence: 99%